Study of the Structure of Crater at the Surface of 12Cr18Ni10Ti Steel Irradiated by High-Power Pulsed Ion Beam; Inorganic Materials: Applied Research; Vol. 9, iss. 3 - Zhidkov M. V. Mikhail; Ligachev A. E. Aleksandr Egorovich; Potemkin G. V. Gely Valerjyanovich; Manokhin S. S. Sergey Sergeevich; Remnev G. E. Gennady Efimovich; Kolobov Yu. R. Yury Romanovich (2018, 2018)
Title screen